The Effectiveness of Deep Breathing Exercise on Lung Expansion Rate in Patients with Respiratory Disorders using Chest Drains - Bahri, Muhammad Saiful; Yulistiani, Mustiah; Widyaningsih, Susana (Proceedings Series on Health & Medical Sciences, 2025)
A chest drain is a medical procedure performed to remove air, fluid, or blood that has accumulated in the pleural cavity, the space between the lungs and the chest wall, to maintain normal lung function. The insertion of a chest drain can cause partial lung collapse or atelectasis. One of the post-surgical care strategies for patients with chest drains is deep breathing exercise therapy. To evaluate the effectiveness of deep breathing exercises on the rate of lung expansion in patients with respiratory disorders using chest drains. This study employed a quasi-experimental design with a pre-test and post-test control group design. The sample consisted of 17 patients with chest drains, selected using total sampling. The measurement tool used was a Peak Flow Meter. Based on the Paired t-test and independent t-test results, the p-value was less than 0.05, indicating significance. The effectiveness test using Cohen's d effect size showed pre-test (1.0) and post-test (3.1) values greater than 0.8, indicating a large effect size. Deep breathing exercise therapy significantly and substantially affects lung expansion rate in patients with respiratory disorders using chest drains.